Identification of the Virulence Landscape Essential for Entamoeba histolytica Invasion of the Human Colon - Thibeaux, Roman; Weber, Christian; Hon, Chung-Chau; Dillies, Marie-Agnès; Avé, Patrick; Coppée, Jean-Yves; Labruyère, Elisabeth; Guillén, Nancy (PLoS pathogens, 2013)
Entamoeba histolytica is the pathogenic amoeba responsible for amoebiasis, an infectious disease targeting human tissues. Amoebiasis arises when virulent trophozoites start to destroy the muco-epithelial barrier by first crossing the mucus, then killing host cells, triggering inflammation and subsequently causing dysentery. The main goal of this study was to analyse pathophysiology and gene expression changes related to virulent (i.e. HM1:IMSS) and non-virulent (i.e. Rahman) strains when they are in contact with the human colon. Transcriptome comparisons between the two strains, both in culture conditions and upon contact with human colon explants, provide a global view of gene expression changes that might contribute to the observed phenotypic differences. The most remarkable feature of the virulent phenotype resides in the up-regulation of genes implicated in carbohydrate metabolism and processing of glycosylated residues. Consequently, inhibition of gene expression by RNA interference of a glycoside hydrolase (β-amylase absent from humans) abolishes mucus depletion and tissue invasion by HM1:IMSS. In summary, our data suggest a potential role of carbohydrate metabolism in colon invasion by virulent E. histolytica.